Effect of vagotomy during Roux-en-Y gastric bypass surgery on weight loss outcomes. Issue 3 (May 2015) - Okafor, Philip N.; Lien, Chueh; Bairdain, Sigrid; Simonson, Donald C.; Halperin, Florencia; Vernon, Ashley H.; Linden, Bradley C.; Lautz, David B.
Summary Background During Roux-en-Y gastric bypasses (RYGB), some surgeons elect to perform a vagotomy to reduce symptoms of gastro-oesophageal reflux (GER). Routine vagotomy during RYGB may independently affect weight loss and metabolic outcomes following bariatric surgery. We aimed to determine whether vagotomy augments percent excess weight loss in obese patients after RYGB. Methods We examined the effect of vagotomy in 1278 patients undergoing RYGB at our institution from 2003 to 2009. Weight and percent excess weight loss (%EWL) were modelled at three months and annually up to five years using a longitudinal linear mixed model controlling for differences in age, gender, initial body mass index (BMI), ideal body weight, and presence of vagotomy. Results Vagotomy was performed on 40.3% of our cohort. Vagotomy patients had significantly lower initial BMI (46.4 ± 6.2 vs. 48.3 ± 7.7 kg/m2, p < 0.001), but there were no other significant differences at baseline. The strongest predictor of %EWL over time was initial BMI, with lower BMI patients exhibiting greater %EWL (p < 0.001). Age and gender effects were also significant, with younger patients (p < 0.04) and males (p < 0.002) attaining greater %EWL. Vagotomy had no effect on %EWL in either simple or multiple regression models. Conclusion Our series suggest that vagotomy does not augment %EWL when performed with RYGB.